Formulasi Sediaan Salep Ekstrak Etanol Daun Alpukat (Persea americana Mill.) Sebagai Antiacne Terhadap Bakteri Staphylococcus aureus - Widianti, Reika Aqni; Nofita, Nofita; Yasir, Angga Saputra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Acne is an inflammatory disease that can occur in certain parts caused by the activity of oil glands that are encircled and aggravated by infection with Staphyloccocus aureus bacteria. An alternative that can be done to treat acne by using plants that have active substances, one of which is avocado leaves (Persea americana Mill.). This study aims to determine the concentration of PEG 400 and PEG 4000 in avocado leaf extract antiacne ointment preparations that are good in inhibiting Staphylococcus aureus bacteria and fulfilling physical evaluation. Extraction of avocado leaf using the percolation method with a 96% ethanol solvent. The concentration used in F I is 1.3%:1%, F II is 1%:1,3%, and F III is 1%:1%. Physical evaluation tests include organoleptic tests, homogeneity, pH, dispersal, adhesion, irritation tests and hedonic tests. Antibacterial activity test using the method of diffusion of wells. The bacterial activity test was carried out by formula I with an inhibitory zone of 25.03 belonging to the very strong category. The results of the antibacterial test were analyzed using ANOVA. The results of the statistical analysis showed a significant difference in inhibition zones, namely the value (P = 0.05) in avocado leaf extract antiacne ointment. Based on the results of the study, it was concluded that the avocado leaf extract antiacne ointment which has the best physical properties and has a large inhibitory activity in formulation I with a concentration of PEG 400 and PEG 400, which is 1.3%: 1%.